The Downside Risk of Heavy Tails induces Low Diversification - Namwon Hyung; Casper G. de Vries (Tinbergen Institute, 2010)
Actual portfolios contain fewer stocks than are implied by standard financial analysis that balances the costs of diversification against the benefits in terms of the standard deviation of the returns. Suppose a safety first investor cares about downside risk and recognizes the heavytail feature of the asset return distributions. Then we show that optimal portfolio sizes are smaller than traditional correlation based diversificationanalysis suggests.
Keywords: G0; G1; C2; 330; Portfolio diversification; downside risk; heavy tails; Portfolio-Management; Risiko; Kapitaleinkommen; Messung; Statistische Verteilung; Theorie